Analisis Pengembangan Model Komunikasi dan Metode Percepatan Pencapaian Adopsi Teknologi Pengendalian Penyakit Layu Bakteri pada Tanam Nilam di Sulawesi Tenggara - Iskandar, Iskandar; Rahman, H. Abdul (Department of Agribusiness Halu Oleo University Kendari Southeast Sulawesi, 2012)
This study aims to determine the model of communication in achieving accelerated adoption of technology control bacterial wilt disease on patchouli-friendly environment in Southeast Sulawesi, identified and analyze multiple communication methods to support acceleration of the achievement of the adoption of control bacterial wilt disease on patchouli-friendly environment in Southeast Sulawesi and analyze and formulate a model of communication and effective communication methods to support acceleration of the achievement of site-specific technology adoption controlling bacterial wilt disease on patchouli-friendly environment Southeast Sulawesi, research. This study was conducted in 2012 in Southeast Sulawesi Kolaka. Siting did purposively, sampling randomly determined from a number of farmers. This study is survey research combined with quasi-experimental studies. Analysis of descriptive and quantitative data. The results showed that the specific communication models to be applied to accelerate the deployment of information technology is the control of bacterial wilt of participatory interactive communication model, this model is based on the needs of the communicator and the communicant; media interest by farmers as a medium of information technology is accelerating print leaflets and polders, the media contains short and brief information so as to increase the knowledge of farmers, is small so it's easy to go everywhere below, can be read again and again whenever necessary, and does not require any device or other means of support when using the communication and application of the model can be implemented and continuous effective if done in coordination with relevant parties ie trainers, farmers and researchers.